2013
DOI: 10.3109/17435390.2013.842267
|View full text |Cite
|
Sign up to set email alerts
|

Nose-to-brain transport of aerosolised quantum dots following acute exposure

Abstract: Nanoparticles are of wide interest due to their potential use for diverse commercial applications. Quantum dots are semiconductor nanocrystals possessing unique optical and electrical properties. Although quantum dots are commonly made of cadmium, a metal known to have neurological effects, potential transport of quantum dots directly to the brain has not been assessed. This study evaluated whether quantum dots (CdSe/ZnS nanocrystals) could be transported from the olfactory tract to the brain via inhalation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 24 publications
0
57
0
Order By: Relevance
“…Previous studies have reported transport of nanoparticles to the OB via the olfactory system in the nose (Elder et al 2009; Hopkins et al 2014; Oberdörster et al 2004) as well as higher levels of Ag in the OB than in the rest of the brain as measured by atomic absorption spectroscopy (Ji et al 2007; Sung et al 2009). Genter et al (2012) visualized Ag in the OB and in cells lining the lateral ventricle via autometallography following intranasal administration and surmised that high Ag deposition in the OB, which is located closer to the inhalation site than the rest of the brain, suggests that Ag particles reach the brain via the nose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported transport of nanoparticles to the OB via the olfactory system in the nose (Elder et al 2009; Hopkins et al 2014; Oberdörster et al 2004) as well as higher levels of Ag in the OB than in the rest of the brain as measured by atomic absorption spectroscopy (Ji et al 2007; Sung et al 2009). Genter et al (2012) visualized Ag in the OB and in cells lining the lateral ventricle via autometallography following intranasal administration and surmised that high Ag deposition in the OB, which is located closer to the inhalation site than the rest of the brain, suggests that Ag particles reach the brain via the nose.…”
Section: Discussionmentioning
confidence: 99%
“…Three possible pathways have been suggested: a ) transcellular transport across sustentacular cells of the olfactory epithelium, b ) paracellular transport through junctions of the olfactory epithelium, or c ) intracellular transport through axonal movement via olfactory nerve fascicles to the synaptic junctions within the OB (Illum 2000; Shepherd 1994). Nanoparticle translocation along axons of olfactory nerve fascicles and accumulation in the OB have been previously studied (Aschner 2009; De Lorenzo 1960; Elder et al 2006, 2009; Hopkins et al 2014; Oberdörster et al 2004; Patel et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…The existence of the nose-to-brain pathway of particle transport has been demonstrated by inhalation experiments in laboratory animals, which observed that nanoparticles depositing on the olfactory epithelium can migrate to the brain along the olfactory bulb (Balasubramanian et al, 2013; Elder et al, 2006; Hopkins et al, 2014; Kao et al, 2012; Moshkin et al, 2014; Oberdorster et al, 2004; Sunderman, 2001; Yu et al, 2007). Experimental studies instilling an aqueous solution of nanoparticles into the nasal cavity of rodents have corroborated this nose-to-brain migration of nanoparticles (Liu et al, 2014; Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The route taken by inhaled nanoparticles to reach the brain is unclear, but there is increasing evidence that metal nanoparticles depositing in the olfactory region in the nasal cavity can migrate to the brain along the olfactory bulb (Hopkins et al, 2014; Oberdorster et al, 2004). Although this nose-to-brain route of exposure has not been confirmed in humans, it has been demonstrated in non-human primates (Dorman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have revealed similar transport and accumulation of aerosolized quantum dots48, ultrafine carbon particles20, Fullerenes47 and intravenously injected AuNPs49 to the mammalian brain. However examination of changes in physiology before and after such delivery has proven to be a challenge.…”
Section: Discussionmentioning
confidence: 96%